Estimativa de produção de serapilheira em uma floresta de várzea no distrito de Arapixuna, Santarém-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The Amazon Basin is the largest hydrographic basin in the world, also featuring one of the largest flooded areas in the globe. Floodplain forests comprise a specific type of floodplain within the Amazon, characterized by being areas of forests periodically flooded by whitewater rivers. In these ecosystems, studies of biomass deposition dynamics are extremely important, as it defines the future trajectory of the net carbon balance of the ecosystem and is also the main route of nutrient transfer from vegetation to soil. The present study aims to quantify biomass production via litter, investigating patterns of seasonal occurrence, as well as its nutritional composition. For this, 12 collectors were installed in 4 plains of floodplain forests and monthly litter collections were carried out over 19 months in a floodplain forest in Arapixuna District, located in the municipality of Santarém-PA. The results showed a high litter production in these forests, with a monthly average of 1,357.8 kg ha -1 and a total production of 1,4487.7 kg ha -1 for the year 2018. A higher production pattern was observed in the flood and lower in the dry season, with the leaves being the most produced fraction, with 57% of the litter biomass composition. Biomass production was positively correlated with some physical factors such as Amazon River flow and water level. There was no seasonal pattern of nutrient concentration in litter, however nutrient analysis showed that calcium (Ca) is the highest concentration in litter with an average of 426 kg ha -1, while phosphorus (P ) has the lowest concentration, with an average of 55 kg ha -1. As for micronutrients, Fe was the most outstanding element (18.47 kg ha -1), while the lowest micronutrient was Zn with an average of 6.69 kg ha -1. These results indicate that environmental factors influence the dynamics of litter production in floodplain areas, and it plays a crucial role in nutrient cycling within this medium. The deposition of material via litter, combined with the flood pulse, brings with it a very important nutrient load for the maintenance of local soils.
Keywords: Biomassa; serapilheira; várzea; CNPQ:: CIÊNCIAS BIOLÓGICAS